Restoration of burned areas in forest management plans - Alloza, J. A.; Vallejo, R. (Desertification in the Mediterranean Region. A …, 2006)
Wildland fire is a major disturbance promoting landscape changes and triggering desertification processes in the Northern Mediterranean basin. Addressing that issue in the long term requires both fire prevention and pot-fire restoration measures. Post-fire restoration should mitigate ecosystem degradation, and improve ecosystem regeneration rate and quality. The impact of wildfires is especially acute in the transition between semi-arid and dry subhumid climates, where dry vegetation fuels facilitate fire spread and water shortage limits post-fire regeneration. In addition, the occurrence of torrential rains produces a high risk of post-fire flash-floods, especially in autumn after summer fires. The major objectives of post-fire restoration are soil and water conservation and increasing ecosystem resistance and resilience in front of fire. Post-fire restoration strategies are defined according to the degradation stage of the ecosystems and the recovery capacity of vegetation. Plant cover regeneration rate highly influence post-fire soil erosion and flooding risk. The abundance of woody resprouters is recognized in eastern Spain as a critical factor to ensure an efficient recovery of plant cover after fire. Post-fire restoration planning is addressed taking into account vegetation fragility to wildfires, together with soil erosion risk and soil moisture availability (physical features). Vegetation fragility is defined both in relation to spontaneous regeneration capacity of plant cover and in relation to the ability of keystone woody species topersist after fire. A synthetic indicator to asses wildland protection and restoration priorities in relation to wildland fires is developed by combining vegetation fragility and physical layers in a GIS. William G. Kepner, Jose L. Rubio, David A. Mouat & Fausto Pedrazzini, eds. Desertification in the Mediterranean Region a Security Issue, : 475 © 2006 Springer. Printed in the Netherlands. 475–488.
The following values have no corresponding Zotero field: periodical: Desertification in the Mediterranean Region. A …
Keywords: degradation (voyant); desertification; erosion; fire; FOREST; Mediterranean; Regeneration; Restoration; Soil